2017
DOI: 10.3390/buildings7040111
|View full text |Cite
|
Sign up to set email alerts
|

The Perceived Benefits of Apps by Construction Professionals in New Zealand

Abstract: Abstract:The construction sector is a key driver of economic growth in New Zealand; however, its productivity is still considered to be low. Prior research has suggested that information and communication technology (ICT) can help enhance efficiency and productivity. However, there is little research on the use of mobile technologies by New Zealand construction workforce. This paper reports findings of an exploratory study with the objective of examining the perceived benefits regarding uptake of apps in New Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…In a survey towards the uptake of mobile computing technology in New Zealand building industry, indicated that adoption of mobile applications provided better client relationship management and satisfaction, which has a positive correlation with sector's overall productivity and profit (Liu, Mbachu, Mathrani, Jones, & McDonald, 2017). Although the basis of analysis covered a very small survey sample, it provided a starting point for encouraging further uptake of multiple mobile technologies in the sector.…”
Section: Ubiquitous Digital Accessmentioning
confidence: 99%
“…In a survey towards the uptake of mobile computing technology in New Zealand building industry, indicated that adoption of mobile applications provided better client relationship management and satisfaction, which has a positive correlation with sector's overall productivity and profit (Liu, Mbachu, Mathrani, Jones, & McDonald, 2017). Although the basis of analysis covered a very small survey sample, it provided a starting point for encouraging further uptake of multiple mobile technologies in the sector.…”
Section: Ubiquitous Digital Accessmentioning
confidence: 99%
“…Smart devices and their related technologies provide enhanced communication and exchanged of information among their users. In the case of the construction sector, Liu et al (2017) highlight the following perceived benefits of the use of smart devices in the New Zealand construction industry: more efficient management of documentation; improved efficiency and accuracy of site inspections and reporting; better client relationship management and satisfaction; better timesheet management for employees and sub-contractors; improved visibility into workforce productivity, performance monitoring and evaluation; reduced liability and risks through accurate and prompt compliance reporting; better pricing and tracking of orders; and real-time tracking for prompt payments.…”
Section: Smart Device In the Construction Industrymentioning
confidence: 99%
“…A critical step towards the implementation of any new paradigm is convincing the decision makers of a company about the benefits of such implementation. Following the survey performed by Liu et al (2017), these benefits could potentially be: more efficient management of documentation, improved efficiency and accuracy of site inspections and reporting, better client relationship management and satisfaction, reduced liability and risks through accurate and prompt compliance reporting.…”
Section: Csfs For a Successful Implementation Of Smart Devices In Construction Projectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al [18] carried out research to examine the perceived benefits of apps by construction professionals in New Zealand. Similarly, a study to assess the use of social customer relationship management by building contractors was embarked upon in Tasmania in [19].…”
Section: Introductionmentioning
confidence: 99%